Feeding habit and Predation Selectivity of Reef Fish Chaetodon octofasciatus in Artificial Patch Reef and Natural Reef of Panjang Island, Jepara - Bramasta, Arrico Fathur Yudha; Munasik, Munasik; Haryanti, Dwi (Jurnal Kelautan Tropis, 2024)
Chaetodon octofasciatus is a species of fish in the Chaetodontidae family, commonly known as an indicator fish in the reef ecosystem as the frequency of its appearance in the wild can interfere with the state of the coral reef ecosystem in the waters. Panjang Island is located in Jepara, Central Java, Indonesia, in which one method of coral reef ecosystem rehabilitation in a a form of Artificial Patch Reef (APR) has been implemented. This study aims to investigate the levels of C. octofasciatus predation on corals in the APR and Natural reef of Panjang Island. We used the LIT (Line Intercept Transect) to measure the density of coral reefs at both locations. The abundance of C. octofasciatus was calculated using the Belt Transect method, while selectivity and bite ratio was observed and counted every 5 minutes. The results shows that C. octofasciatus from natural reefs have the highest predation rate (185 bites/5 min) and mostly eat the coral with lifeform massive while the ones from APR shows 144 bites/5 min and mostly eat the coral with lifeform Acropora branching. This selectivity could be due to the availability of corals in both areas. While massive corals were highly available in the natural reefs, branchich corals esp. Acropora is mostly planted in the APR. A more diverse coral lifeform in the natural reef also showed the type of corals that are less selected by C. octofasciatus such as submassive corals and Acropora tabulate, as well as corals with the foliose life form.